DISCRIMINANT STOCK PRICE: FINANCIAL RATIO OF PERFORMANCE - Pangestu, Dodo; Purdianto, Ario; Komara, Acep; Parlina, Nurhana Dhea (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
Long-Term Debt to Equity Ratio (LTDER) is a capital structure ratio used to determine the proportion of a company's funding sources. Return On Assets (ROA) is a ratio that measures a company's ability to generate net income based on a certain level of assets. This study examines the effect of Long-Term Debt to debt-to-equity ratio (LTDER) and Return on Assets (ROA) on stock prices. The objects of this research are property and real estate sector companies registered on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This research method uses quantitative research with secondary data. The population in this study was 83 companies. This sample was taken using the purposive sampling method. There are 11 companies as samples. The data analysis technique used is multiple linear regression and hypothesis testing. The results of this study indicate that the Long-Term debt-to-equity ratio (LTDER) has a non-significant negative effect on stock prices. In contrast, Return on Assets (ROA) significantly impacts stock prices. Simultaneously, it shows that the long-term debt-to-equity ratio (LTDER) and return on assets (ROA) substantially affect stock prices.